2023
DOI: 10.1007/s10661-023-11828-z
|View full text |Cite
|
Sign up to set email alerts
|

Response of streamflow and nutrient loads in a small temperate catchment subject to land use change

Gebiaw T. Ayele,
Bofu Yu,
Andy Bruere
et al.

Abstract: The aim of this study was to quantify the effect of land use change (LUC) implemented to meet nutrient load targets for a freshwater lake in New Zealand. We used the Soil and Water Assessment Tool (SWAT) model in combination with a non-parametric statistical test to determine whether afforestation of 15% of a subcatchment area was adequate to meet assigned nutrient load targets. A regional management authority set nutrient load targets of reduction in total nitrogen (TN) by 0.9 t yr−1 and reduction in total ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
1
0
0
Order By: Relevance
“…Generally, it was confirmed that woodlands, both coniferous and deciduous, could accelerate purification effects on stream water quality, as reported previously by [87,88]. Forests provide an accumulation of nitrogen, phosphorus, and metallic elements [89], mainly due to tree uptake [90] and the presence of litter layerand organic-rich soils, supporting complex and differentiated soil microbial communities [91]. However, it must be emphasized that several factors influence the purification effects of forests, such as management practices [92], tree species composition [93], and the spatial configuration of woodlands [94], which could be also a reason behind the relatively high variability of forested sites in terms of water quality.…”
Section: Spatial Variability Evaluationsupporting
confidence: 80%
“…Generally, it was confirmed that woodlands, both coniferous and deciduous, could accelerate purification effects on stream water quality, as reported previously by [87,88]. Forests provide an accumulation of nitrogen, phosphorus, and metallic elements [89], mainly due to tree uptake [90] and the presence of litter layerand organic-rich soils, supporting complex and differentiated soil microbial communities [91]. However, it must be emphasized that several factors influence the purification effects of forests, such as management practices [92], tree species composition [93], and the spatial configuration of woodlands [94], which could be also a reason behind the relatively high variability of forested sites in terms of water quality.…”
Section: Spatial Variability Evaluationsupporting
confidence: 80%